Therapeutic effect of postoperative adjuvant transcatheter arterial chemoembolization based on the neutrophil-to-lymphocyte ratio - Feng, Guo-Ying; Shi, Zheng-Rong; Zhao, Yu-Fei; Chen, Kai; Tao, Jie; Wei, Xu-Fu; Cheng, Yu (Frontiers in Surgery, 2023)
Aim: To evaluate the feasibility of the preoperative neutrophil-to-lymphocyte ratio (NLR) as an index to guide postoperative adjuvant transcatheter arterial chemoembolization (PA-TACE) in patients with liver cancer. Methods: We recruited a total of 166 patients with liver cancer who underwent surgery alone or surgery plus PA-TACE between January 2013 and June 2017 and compared the 1, 2, and 3-year recurrence-free survival (RFS) and overall survival (OS) between patients with high and low NLRs, surgery and surgery plus PA-TACE groups, and relevant subgroups using the Kaplan–Meier method. We also evaluated the independent factors affecting the prognosis of liver cancer after surgery using a Cox risk ratio model and correlation between NLR levels and high-risk recurrence factors of liver cancer with logistic regression analysis. Results: The 1, 2, and 3-year RFS rates were all significantly higher in the low-NLR group compared to the high-NLR group (P < 0.05). However, the 1, 2, and 3-year OS rates were similar in the low- and high-NLR groups (P > 0.05). After propensity score matching, the 1, 2, and 3-year RFS and OS rates were significantly better in patients treated with surgery plus PA-TACE compared with surgery alone (P < 0.05). The 1, 2, and 3-year RFS and OS rates were also significantly better in the surgery plus PA-TACE subgroup compared with the surgery-alone subgroup in the high-NLR group (P < 0.05), but there was no significant difference in RFS or OS between the surgery plus PA-TACE and surgery-alone subgroups at 1, 2, and 3 years in the low-NLR group (P > 0.05). Conclusion: PA-TACE can improve the prognosis of patients with a high preoperative NLR (≥2.5), but has no obvious benefit in patients with low preoperative NLR (<2.5). This may provide a reference for clinical selection of PA-TACE.